Keterlibatan Keluarga dalam Pelayanan Kesehatan Primer : Scoping Review - Catharina Guinda Diannita; Evanny Indah Manurung; Erniyati Fangidae (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT Primary health care is the first form of contact of individuals, families, or communities with the health care service. Optimal primary health care can be achieved, one of which is with the support of family members and clients. Identify family and client involvement in efforts to improve primary health care.Searches of three databases includes EBSCOhost, PubMed and JSTOR, with criteria for primary research, English articles published in 2013-2023. The articles included in this study are articles that discuss family involvement and client involvement in primary health care. The articles found then analyzed using qualitative methods of content analysis. 11 research articles were qualified, and analysis was conducted, so that three main themes of family involvement in primary health care were found: (i) role in communication, (ii) collaboration of families, clients, and primary health care providers, (iii) barriers to family involvement. Families provide communication support as well as collaboration and partnership between families and health professionals. Although not all primary health services are able to collaborate optimally and find obstacles to involve families and clients, efforts to strengthen basic health services, improve the quality and standards of human resources, clarify the duties and responsibilities of health workers and plan programs that involve families and clients in care efforts are carried out to overcome obstacles and improve the quality of services. Keywords: Patient Engagement, Family Engagement, Primary Health Care ABSTRAK Pelayanan kesehatan primer merupakan bentuk kontak pertama individu, keluarga atau masyarakat dengan sistem pelayanan. Pelayanan kesehatan primer yang optimal dapat tercapai salah satunya dengan adanya dukungan dari anggota keluarga dan klien. Tujuan untuk mengidentifikasi keterlibatan keluarga dan klien dalam upaya meningkatkan pelayanan kesehatan primer. Metode penelitian dengan pencarian dari tiga database meliputi EBSCOhost, PubMed dan JSTOR, dengan kriteria artikel penelitian primer, bahasa Inggris yang dipublikasikan pada tahun 2013-2023. Artikel yang diikutsertakan dalam studi ini adalah artikel yang membahas mengenai keterlibatan keluarga maupun keterlibatan klien dalam pelayanan kesehatan primer. Artikel yang ditemukan kemudian dianalisa dengan menggunakan metode kualitatif konten analisis. 11 artikel penelitian memenuhi syarat dan dilakukan analisis, sehingga ditemukan tiga tema utama keterlibatan keluarga dalam pelayanan kesehatan primer: (i) peran dalam komunikasi, (ii) kolaborasi keluarga, klien dan penyedia layanan kesehatan primer, (iii) hambatan keterlibatan keluarga. Keluarga memberikan dukungan komunikasi serta kolaborasi dan partnership antara keluarga dan tenaga kesehatan professional. Meskipun tidak semua pelayanan kesehatan primer mampu berkolaborasi secara optimal dan menemukan hambatan untuk ikut melibatkan keluarga dan klien, namun upaya tenaga kesehatan serta merencanakan program yang turut melibatkan memperkuat pelayanan kesehatan dasar, meningkatkan kualitas dan standar SDM, memperjelas tugas dan tanggung keluarga dan klien dalam upaya perawatan dapat dilakukan untuk mengatasi hambatan dan meningkatkan kualitas pelayanan. Kata kunci: Patient Engagement, Family Engagement, Primary Health Care